2010
DOI: 10.1007/s11010-010-0413-x
|View full text |Cite
|
Sign up to set email alerts
|

Newly identified tumor-associated role of human Sharpin

Abstract: In order to discover previously unidentified cancer-associated genes, we analyzed genome-wide differences in gene expression between tumor biopsies and normal tissues. Among those differentially regulated genes, we identified Sharpin (Shank-associated RH domain-interacting protein) as a commonly up-regulated gene in multiple human cancer types. Although rat Sharpin is reported to interact with Shank1, a multidomain scaffold protein localized in postsynaptic densities, its exact roles are unknown. Whereas human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
62
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 13 publications
6
62
1
Order By: Relevance
“…Upregulation of SHARPIN in HCC [22] was confirmed in a previous study by our group [25] , in which SHARPIN expression was shown to be positively correlated with larger hepatic tumors, a higher histological grade, and therefore HCC progression. In recently published work, we examined the role of SHARPIN in the malignant phenotype characteristic of HCC [25] .…”
Section: Sharpin: Newly Identified Mediator Of Hcc Invasion and Progrsupporting
confidence: 68%
See 1 more Smart Citation
“…Upregulation of SHARPIN in HCC [22] was confirmed in a previous study by our group [25] , in which SHARPIN expression was shown to be positively correlated with larger hepatic tumors, a higher histological grade, and therefore HCC progression. In recently published work, we examined the role of SHARPIN in the malignant phenotype characteristic of HCC [25] .…”
Section: Sharpin: Newly Identified Mediator Of Hcc Invasion and Progrsupporting
confidence: 68%
“…SHARPIN was identified as a commonly upregulated gene in liver and ovarian cancer by cDNA microarray analysis, although the case-sample size in that study was not large enough to allow definite conclusions [22] . SHARPIN is also amplified and upregulated in invasive ductal breast cancers [23] .…”
Section: Sharpin: Newly Identified Mediator Of Hcc Invasion and Progrmentioning
confidence: 92%
“…The observation that suppression of NF-κB activation by NF-κB decoy oligonucleotide reduced the size of the metastatic nodules of LM8 cells in the lung is consistent with our results (7). It has been recently shown that the introduction of SHARPIN, a component of LUBAC, enhanced the anchorageindependent growth of CHO cells, although the amounts of the other components of LUBAC were not determined (42). Collectively, LUBAC-induced NF-κB activation might be involved not only in the attachment of LM8 cells to the lung, but also in the other aspects of metastasis after extravasation, such as invasion activity and/or anoikis resistance, in our experimental model.…”
Section: Discussionmentioning
confidence: 67%
“…SHARPIN gene encodes for phosphoproteins that are conserved mainly in the cytoplasm (Lim et al, 2001). Up-regulation of this gene in multiple human cancer types have been addressed for tumour-associated role in carcinogenesis (Jung et al, 2010). However, this gene has been identified to regulate intrinsic caspasedependent mitochondria pathway leading to keratinocyte apoptosis (Liang and Sundberg, 2011).…”
Section: Discussionmentioning
confidence: 99%